2006
DOI: 10.1111/j.1538-7836.2006.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes derived from human embryonic stem cells: a genetically tractable system to study megakaryocytopoiesis and integrin function

Abstract: Summary. Background: The platelet fibrinogen receptor, a heterodimer consisting of integrin subunits a IIb and b 3 , is required for platelet aggregation, spreading, and hemostasis. Platelet agonists such as thrombin and adenosine diphosphate (ADP) lead to the activation of a IIb b 3 , thereby enhancing its affinity and avidity for binding fibrinogen (inside-out signaling). Furthermore, fibrinogen binding to a IIb b 3 triggers cytoskeletal changes and granule release (outside-in signaling). Aim: Genetic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 30 publications
1
116
0
3
Order By: Relevance
“…48,49 The mechanisms that lead to ␣ IIb ␤ 3 activation in megakaryocytes are incompletely understood, but platelet agonists enhance ␣ IIb ␤ 3 -dependent responses in megakaryocytes. 48,50 In this regard, we found that thrombin enhanced megakaryocyte adherence and spreading on immobilized fibrinogen. However, unlike cPAF treatment, binding and spreading of megakaryocytes in response to thrombin was not inhibited by a PAFR blocker ( Figure S6).…”
Section: Discussionmentioning
confidence: 81%
“…48,49 The mechanisms that lead to ␣ IIb ␤ 3 activation in megakaryocytes are incompletely understood, but platelet agonists enhance ␣ IIb ␤ 3 -dependent responses in megakaryocytes. 48,50 In this regard, we found that thrombin enhanced megakaryocyte adherence and spreading on immobilized fibrinogen. However, unlike cPAF treatment, binding and spreading of megakaryocytes in response to thrombin was not inhibited by a PAFR blocker ( Figure S6).…”
Section: Discussionmentioning
confidence: 81%
“…Two major quantitative roadblocks persist in the development of donorindependent PLTs for therapeutic use: (1) generating sufficient numbers (;3 3 10 8 ) of human MKs to support the production of 1 PLT transfusion unit (;3 3 10 11 PLTs); and (2) generating physiological numbers of functional human PLTs (;10 3 ) per MK. 18 The development of human embryonic stem cell cultures (hESC), 44,46 and more recently, hiPSC 47 (Feng Q et al, manuscript submitted 2014) offer a physiologically relevant and potentially unlimited source of progenitor cells that can be differentiated into human MKs in vitro to address the first quantitative roadblock. 48 Indeed, because PLTs are anucleate, PLT bioreactor-derived units could be irradiated prior to infusion, addressing concerns that cellular products derived from hESC or hiPSCs could be oncogenic or teratogenic.…”
Section: Discussionmentioning
confidence: 99%
“…The first relies on external signals provided by cytokines or stromal cells to mimic embryonic development and direct sequential differentiation of hPSCs into MKs, a process designated as "directed differentiation" (DD) [227][228][229][230][231]. These protocols are impaired by a lack of efficiency, low purity of the MKs and often rely on serum and xenogenic feeder cells.…”
Section: Mks and Platelets From Human Pluripotent Stem Cellsmentioning
confidence: 99%